2008
DOI: 10.1530/rep-07-0433
|View full text |Cite
|
Sign up to set email alerts
|

Xenografting of sheep testis tissue and isolated cells as a model for preservation of genetic material from endangered ungulates

Abstract: Recovery of germ cells could be an option for preservation of the genetic pool of endangered animals. In immature males, xenografting of testis tissue provides the opportunity to recover sperm from these animals. In adult animals, xenografting has been less successful, but de novo morphogenesis of functional testis tissue from dissociated testis cells could be an alternative. To assess the potential use of these techniques in endangered bovid species, the domestic sheep was used as a model. Testes from 2-week-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 36 publications
10
74
0
Order By: Relevance
“…The flat strips of testis from prepubertal ram lambs in this study survived engraftment and developed similarly to that reported for 1 mm 3 pieces from newborn lambs , Arregui et al 2008. Both in this study and that of Arregui et al (2008), grafts were collected up to 16 weeks after transplantation, and percentage of grafts that were recovered was 97 and 96% respectively.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The flat strips of testis from prepubertal ram lambs in this study survived engraftment and developed similarly to that reported for 1 mm 3 pieces from newborn lambs , Arregui et al 2008. Both in this study and that of Arregui et al (2008), grafts were collected up to 16 weeks after transplantation, and percentage of grafts that were recovered was 97 and 96% respectively.…”
Section: Discussionsupporting
confidence: 78%
“…The flat strips of testis from prepubertal ram lambs in this study survived engraftment and developed similarly to that reported for 1 mm 3 pieces from newborn lambs , Arregui et al 2008. Both in this study and that of Arregui et al (2008), grafts were collected up to 16 weeks after transplantation, and percentage of grafts that were recovered was 97 and 96% respectively. In this study, elongated spermatids were not detected at 8 weeks, but were detected at 16 weeks in 16% of tubules, while in the Arregui et al (2008) study they were not detected at 8 weeks and were present at 16 weeks in 19% of tubules.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Studies of spermatogenesis were long hampered because of a lack of powerful in vitro and in vivo assay systems until an exciting new technique, a method for the transplantation of germ cells from one animal to another, was established [1]. It was shown that germ cells from hamsters, rabbits, dogs, sheep or bulls can be heterotransplanted into the mouse, which then survive and result in long-lasting spermatogenesis in the host testes, proliferate and differentiate into spermatozoa or elongated spermatids [2][3][4][5]. Germ-cell transplantation has also been successfully performed in cat, goat, pig, monkey and human testes [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The approach has especially been successful using neonatal/immature donors (Fig. 5), from laboratory animals to domestic animals, primates, and even humans (Honaramooz et al, 2002aSchlatt et al, 2002;Oatley et al, 2004;Snedaker et al, 2004;Rathi et al, 2005Rathi et al, , 2006Arregui et al, 2008;Abrishami et al, 2010b). .…”
Section: Testis Tissue (Xeno)graftingmentioning
confidence: 99%